2005
DOI: 10.1088/0953-2048/18/12/023
|View full text |Cite
|
Sign up to set email alerts
|

The strain effect on critical current in YBCO coated conductors with different stabilizing layers

Abstract: The tensile strain dependences of the critical current (I c ) in YBa 2 Cu 3 O 7−δ (YBCO) coated conductors fabricated by using the rolling-assisted biaxially textured Ni-W substrates (RABiTS)-pulsed laser deposition (PLD) method were examined at 77 K and in self magnetic field. Cu and stainless steel layers were used as stabilizers to the YBCO coated conductor, and the effects of stabilizing layers on the strain tolerance of I c were investigated, compared with the case without a stabilizing layer. The laminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
74
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 13 publications
11
74
1
Order By: Relevance
“…In 2005 Shin et al [62], investigated the effect of stabilizer layer on critical current for a PLD-Y123 CC deposited onto a 50 μm thick NiW substrate. In particular, their results showed that a 70 μm thick laminated SS tape significantly increases the irreversible tensile strain, because SS contracts more than NiW, inducing a large precompression in the superconductor layer.…”
Section: Strategies To Reduce Hysteretic Lossesmentioning
confidence: 99%
“…In 2005 Shin et al [62], investigated the effect of stabilizer layer on critical current for a PLD-Y123 CC deposited onto a 50 μm thick NiW substrate. In particular, their results showed that a 70 μm thick laminated SS tape significantly increases the irreversible tensile strain, because SS contracts more than NiW, inducing a large precompression in the superconductor layer.…”
Section: Strategies To Reduce Hysteretic Lossesmentioning
confidence: 99%
“…Under self field at 77 K, electromechanical properties evaluation of the CC tapes under tension was done adopting the test rig reported in [14]. Loading frame was mounted on a universal test machine and load was applied to the sample by moving the pull rod.…”
Section: Methodsmentioning
confidence: 99%
“…Strain effects in superconducting wires/tapes have been intensively investigated by adopting different testing procedures [14][15][16][17]. Recently, fundamental stress-strain measurements on NbTi/Nb 3 Sn wires were completed as international standards (IEC 61788-6) within the framework of IEC/TC90 and VAMAS/TWA 16 with the key task on assessment of the sensing system resolution, accuracy and precision when measuring the elastic modulus [13].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the ε irr significantly increased with an addition of stabilizer and also the improvement depends on stabilizer material adopted [19,20]. Primarily, substrate holds the whole CC superconductor composite, thus it influences the mechanical behavior of the whole tape especially for Ag-stabilized CC tape samples [21].…”
Section: Introductionmentioning
confidence: 99%